Economic Impact of Diagnostic Imaging in the Workup of Uncomplicated Bell's Palsy - Kazemian, Elycia; Schaffer, Hollie Marie; Wozniak, Amy; Leonetti, John P. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Our primary objective is to identify the costs associated with imaging in the diagnostic workup of uncomplicated Bell's palsy. Our secondary objective is to identify a dollar amount spent on extraneous diagnostic testing on a state and national level.Design and Setting Retrospective chart analysis was performed at our tertiary care medical center between 2007 and 2018. International Statistical Classification of Diseases-10 code G51.0 was used to identify patients with Bell's palsy seen by the senior author. A total of 163 patients were divided into two groups: those having received imaging and those diagnosed without imaging. The imaging group was then further subdivided by imaging modality: computed tomography (CT) only, magnetic resonance imaging (MRI) only, or both. There was a total of 138 scans in 115 patients. To quantify the amount spent by insurance companies or patients on these scans, net expected pay (NEP) for each modality was used as a representation of cost. The NEP for a CT was $618. The NEP for an MRI was $1,119. The NEP for both scans was $1,737. We extrapolated our results to a state and national level.Main Outcome Measurements Cost of workup; state and national economic burden.Results Extrapolating our data, we forecast that in Illinois and in the United States, over $2 million and $53 million, respectively, are spent on unnecessary imaging.Conclusion By highlighting an unnecessary financial burden, our study provides concrete evidence to support the American Academy of Otolaryngology's recommendation that clinicians should not perform routine imaging studies when diagnosing uncomplicated Bell's palsy.
Keywords: Bell's palsy; facial paralysis; emergency medicine; computerized tomography; magnetic resonance imaging; cost data; neurology; urgent care; otolaryngology